Perfil, motivaciones y expectativas de los alumnos de primer curso de la Escuela Universitaria de Biblioteconomía y Documentación de la Universidad Complutense de Madrid (curso 2001-2002) - Tejada Artigas, Carlos (Revista General de Información y Documentación, 2003)
A profile of students at the Escuela Universitaria de Biblioteconomía y Documentación at The Universidad Complutense de Madrid was carried out on the basis of the results of a survey completed by students in their first year at this institution in the academic year 2001-2002. The paper describes demographic aspects, motivation and the expectations held with regard to these studies by the students, their appreciation of the profession’s social recognition and, finally, the degree to which these are included in the School.